Estudo da resposta imune e do tipo de papiloma vírus humano na evolução de pacientes conizadas por neoplasia intra-epitelial cervical grau III. - Maluf, Paulo José (2007)
Uterine cervix cancer remains the third most common neoplasia and the fourth cause of death due to cancer among Brazilian women, althougth a decreasin incidence, morbidity and mortality have been observed over the last decades. Human papillomavirus (HPV) has been indicated as its most important causal factor. The local and systemic host immune response seem to play an important role in controlling HPV infection and the progression to cervical intraepithelial neoplasia (CIN). We analyzed 35 cases of CIN III in patients who have been undergone conization. Immunohistochemistry was used to detect CD3, CD8, CD45RO, CD20 and CD68 antibodies and the iNOS enzyme. The slides were evaluated by two observers and the agreement between them was calculated by means of the Kappa coefficient and stablished as 0,83. We also performed the polymerase chain reaction (PCR) to detect HPV DNA subtypes 6, 11, 16 and 18, in 14 out of the 35 patients. We found a stronger expression of CD3-positive T lymphocytes in patients with CIN III who relapsed after conization, suggesting that this may be a predictive factor of a worse outcome evolution. We did not find any statistical differences in the expression of CD20, CD68, CD45RO, CD8 and iNOS. We also observed correlation with high-risk HPV infection, particularly subtype 18, and relapse recurrence of CIN after conization, and this may also be considered a predictor of a worse outcome.